(untitled) (Vietnam Journal of Community Medicine, 2022)
Objects: This study aimed to assess the status and associated factors effecting the compliance with regulations on surgical antibiotics prophylaxis at Thu Duc city hospital in 2021. Methods: A descriptive cross-sectional study was conducted among 270 medical records of patients who had had surgery indications and underwent clean, clean-contaminated procedures at Surgical departments of the hospital from January to June 2021. Results: The rate of compliance with all five criteria on the use of prophylactic antibiotics at the hospital was only 17%. While most cases had appropriate indications, route of administration and dosage (the rates were 92.2%, 95.5% and 85.9%, respectively), the appropriate antibiotics election rate was only 77%. Moreover, the proportion of compliance with medication regimens was significantly low at 17.8%. The adherence rate was higher in patients who were over 60 years old, had cleancontaminated surgery, emergency surgery and length of hospital stay more than one day before and ive days after surgery. Conclusions: Improving the antibiotic management program at the hospital is very necessary for the current period, focusing on monitoring the use of antibiotics and training doctors on rational, safe and effective antibiotic use.